2017
DOI: 10.1002/1873-3468.12831
|View full text |Cite
|
Sign up to set email alerts
|

hSnd2 protein represents an alternative targeting factor to the endoplasmic reticulum in human cells

Abstract: Recently, understanding of protein targeting to the endoplasmic reticulum (ER) was expanded by the discovery of multiple pathways that function in parallel to the signal recognition particle (SRP). Guided entry of tail-anchored proteins and SRP independent (SND) are two such targeting pathways described in yeast. So far, no human SND component is functionally characterized. Here, we report hSnd2 as the first constituent of the human SND pathway able to support substrate-specific protein targeting to the ER. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
121
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(150 citation statements)
references
References 55 publications
28
121
0
Order By: Relevance
“…Δsgt2 cells exhibited a more modest defect in mediating rapid Bos1 targeting and insertion into the ER (Fig EV4C and D), consistent with previous observations (Kohl et al, 2011;Kiktev et al, 2012;Yeh et al, 2014). As reported, alternative pathways could enable the targeting of TAs when Sgt2 or Get3 was deleted (Aviram et al, 2016;Haßdenteufel et al, 2017), which may account for the observed TA targeting at steady state.…”
Section: Cytosolic Hsp70 Is Important For the Biogenesis Of Get Substsupporting
confidence: 90%
“…Δsgt2 cells exhibited a more modest defect in mediating rapid Bos1 targeting and insertion into the ER (Fig EV4C and D), consistent with previous observations (Kohl et al, 2011;Kiktev et al, 2012;Yeh et al, 2014). As reported, alternative pathways could enable the targeting of TAs when Sgt2 or Get3 was deleted (Aviram et al, 2016;Haßdenteufel et al, 2017), which may account for the observed TA targeting at steady state.…”
Section: Cytosolic Hsp70 Is Important For the Biogenesis Of Get Substsupporting
confidence: 90%
“…Of note, we observed that ∼30-40% of b5-RR molecules are localized to ER, even in the absence of functional GET system. This partial dependence on the GET components is in line with the idea that multiple selection filters are used by the GET machinery to assure correct targeting (Rao et al, 2016), and that alternative pathways, involving SRP, hSnd2 and/or unassisted membrane integration, exist for ER TA protein targeting in the absence of GET (Casson et al, 2017;Hassdenteufel et al, 2017).…”
Section: Results and Discussion Get-dependent Mislocalization Of Cytosupporting
confidence: 67%
“…with the N-terminus in the lumen. These findings can be explained by recent reports suggesting that the SRP and the Sec translocon are involved in the targeting of some TA proteins, including cytochrome b5, to the ER (Casson et al, 2017;Hassdenteufel et al, 2017). Thus, it might be that the Sec translocon mediates an integration of a sub-population of b5-RR into the ER membrane in the wrong topology.…”
Section: Results and Discussion Get-dependent Mislocalization Of Cytomentioning
confidence: 87%
See 1 more Smart Citation
“…Such a redundancy among several parallel potential pathways was demonstrated lately for the insertion pathway of ER TA proteins. The newly discovered SND pathway (hSND in humans) can complement the loss of the Get/TRC40 or SRP pathway and most probably even the disruption of both pathways together …”
Section: Discussionmentioning
confidence: 99%